1996
DOI: 10.1002/j.2050-0416.1996.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

RELATIONSHIP BETWEENFUSARIUMINFESTATION OF BARLEY AND THE GUSHING POTENTIAL OF MALT

Abstract: Fifty barley samples, displaying a range of 0 to 100% kernels infested with Fusarium. were collected in North Dakota, South Dakota, and Minnesota during the harvest of 1994. Samples were micromalted, and the levels of the fungal metabolites, deoxynivalenol and ergosterol, were determined. Fusarium infestation and the levels of fungal metabolites were evaluated as predictors of gushing in laboratory trials. Malt samples which were infested with Fusarium or contaminated with the fungal metabolites exhibited a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 11 publications
1
54
1
3
Order By: Relevance
“…5). This finding is inconsistent with the results of Schwarz et al 28 who found strong correlation between the DON level and the gushing potential of malt produced from North American barley samples. Most of the samples analyzed in this study were grown in Finland.…”
Section: Hydrophobin Levels In Barley and Malt Samples Compared To Gucontrasting
confidence: 99%
See 4 more Smart Citations
“…5). This finding is inconsistent with the results of Schwarz et al 28 who found strong correlation between the DON level and the gushing potential of malt produced from North American barley samples. Most of the samples analyzed in this study were grown in Finland.…”
Section: Hydrophobin Levels In Barley and Malt Samples Compared To Gucontrasting
confidence: 99%
“…This is probably due to the production of hydrophobins during the malting process, which could be concluded from the lower hydrophobin levels detected in the barleys compared to those of the corresponding malts (data not shown). Previous studies also support this conclusion because fungi, especially fusaria, have been shown to proliferate and to produce mycotoxins and gushing factors in the malting conditions 12,23,28,30 . Furthermore, no connection was found between the results of the hydrophobin ELISA and the deoxynivalenol (DON) contents of the malts (data not shown).…”
Section: Hydrophobin Levels In Barley and Malt Samples Compared To Gumentioning
confidence: 77%
See 3 more Smart Citations